2010
DOI: 10.1016/j.jaci.2009.07.061
|View full text |Cite
|
Sign up to set email alerts
|

Atypical presentation of IL-12 receptor β1 deficiency with pneumococcal sepsis and disseminated nontuberculous mycobacterial infection in a 19-month-old girl born to nonconsanguineous US residents

Abstract: Atypical presentation of IL-12 receptor β1 deficiency with pneumococcal sepsis and disseminated nontuberculous mycobacterial infection in a 19-month-old girl born to nonconsanguineous US residents

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Several reports have shown that patients who had defects in these pathways developed serious and sometimes fatal infections with MTBC and NTM (142,144,309).…”
Section: Gamma Interferon and Interleukin-12 Receptor Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have shown that patients who had defects in these pathways developed serious and sometimes fatal infections with MTBC and NTM (142,144,309).…”
Section: Gamma Interferon and Interleukin-12 Receptor Defectsmentioning
confidence: 99%
“…Gruenberg and colleagues (142) described a second child who, at 19 months of age, was diagnosed with MAC and Streptococcus pneumoniae infection due to an IL-12R␤1 mutation (142). The case represented the first documented case of sepsis due to S. pneumoniae in a patient with an IL-12R␤1 deficiency.…”
Section: Gamma Interferon and Interleukin-12 Receptor Defectsmentioning
confidence: 99%
“…It has since been reported in patients from Argentina, Belgium, United States, Poland and the United Kingdom [Rosenzweig et al, 2006; Haerynck et al, 2008; Yancoski et al, 2009; Gruenberg et al, 2009; de Beaucoudrey et al, 2010]. A founder effect has been proposed for this mutation because its distribution is restricted to Europeans and to individuals from European ancestry living in former European colonies.…”
Section: Il12rb1 Mutationsmentioning
confidence: 99%
“…In our opinion, the best method to address this issue would involve the use of PBMCs from patients with a deficiency in IL-12 or IL-12 receptor (IL-12R), since we could then exclude that the NK cells used in the experiments had been activated at any time in vivo by IL-12. We have previously described a 19-month-old patient with an IL-12Rβ1 deficiency due to a complex mutation at exon 14 in the IL12RB1 gene (c.1623_1624delinsTT; p.Q541X) (9). We showed that IFN-γ production was markedly decreased after stimulation of PBMCs with phytohemagglutinin (PHA) or PHA plus IL-12 and that there was diminished STAT4 phosphorylation after IL-12 stimulation (9).…”
mentioning
confidence: 99%